Coherent THz communication at 200 GHz using a frequency comb, UTC‐PD and electronic detection. Issue 5 (1st February 2014) - Ducournau, G.; Yoshimizu, Y.; Hisatake, S.; Pavanello, F.; Peytavit, E.; Zaknoune, M.; Nagatsuma, T.; Lampin, J.‐F.
Abstract : A coherent terahertz (THz) link at 200 GHz, with a variable data rate up to 11 Gbit/s, featuring a very high sensitivity at the receiver, is investigated. The system uses a quasi‐optic unitravelling carrier photodiode (UTC‐PD) emitter and an electronic receiver. The coherent link relies on an optical frequency comb generator at the emission to produce an optical beat note with 200 GHz separation, phase‐locked with the receiver. Bit error ratio testing has been carried out using an indoor link configuration, and error‐free operation is obtained up to 10 Gbit/s with a received power <2 µW.